Islamic Educational Values in Caring for Children with Disabilities: A Literature-Based Qualitative Study - Fathul Khair; Ni Wayan Wiwin Asthiningsih; Imam Hakam; Risma Amalia Safitri (Journal of Indonesian Islamic Studies, 2026)
Islamic Religious Education (IRE) is a fundamental right for all children, including those with disabilities; however, its implementation remains limited and often lacks adaptive, inclusive approaches. While previous studies have primarily focused on normative discussions of IRE for children with disabilities, there has been insufficient attention to integrating Islamic educational values into practical caregiving strategies. This study, titled Islamic Educational Values in Caring for Children with Disabilities: A Literature-Based Qualitative Study, aims to explore: (1) the core Islamic educational values relevant to children with disabilities, and (2) practical strategies for incorporating these values into caregiving practices. Using a qualitative approach, the research analyzes scholarly books, journal articles, and relevant documents through content analysis, with data reduction, display, and conclusion drawing, supported by source triangulation to ensure validity. The findings reveal that key Islamic educational values for children with disabilities include faith (iman), piety (taqwa), patience, responsibility, and moral conduct. These values can be implemented through adaptive strategies such as individualized instruction, habituation, demonstration, play-based learning, and continuous guidance. The study highlights the crucial role of families and educators in creating inclusive, supportive, and value-oriented learning environments. This research contributes to an integrative framework that links Islamic educational values with caregiving strategies, offering both theoretical insights and practical guidance for parents, educators, and policymakers in promoting inclusive Islamic education for children with disabilities.